Representasi Identitas Etnik Dalam Sastra Indonesia Modern - Muhammad Murdani; Indah Ayu Lestari (Yayasan Grace Berkat Anugerah, 2025)
Indonesia is known as a multiethnic country that has extraordinary cultural richness, consisting of hundreds of ethnic groups, regional languages, and local traditions that coexist in one national unit. In this context, literature plays an important role as a medium of expression and reflection of society's collective identity. Modern Indonesian literature, especially those that developed from the post-independence era to the contemporary era, is not only a space to narrate individual experiences, but also a means to represent social dynamics, including the issue of ethnic identity. The representation of ethnic identity in literary works can be seen as a reflection of how society interprets diversity and how certain ethnic groups are positioned within the broader social structure